Cell-Laden Hydrogel as a Clinical-Relevant 3D Model for Analyzing Neuroblastoma Growth, Immunophenotype, and Susceptibility to Therapies - Marrella, Alessandra; Dondero, Alessandra; Aiello, Maurizio; Casu, Beatrice; Olive, Daniel; Regis, Stefano; Bottino, Cristina; Pende, Daniela; Meazza, Raffaella; Caluori, Guido; Castriconi, Roberta; Scaglione, Silvia (Frontiers in Immunology, 2019)
High risk Neuroblastoma (NB) includes aggressive, metastatic solid tumors of childhood. The survival rate improved only modestly, despite the use of combination therapies including novel immunotherapies based on the antibody-mediated targeting of tumor-associated surface ligands. Treatment failures may be due to the lack of adequate in vitro models for studying, in a given patient, the efficacy of potential therapeutics, including those aimed to enhance anti-tumor immune responses. We here propose a 3D alginate-based hydrogel as extracellular microenvironment to evaluate the effects of the three-dimensionality on biological and immunological properties of NB cells. NB cell lines grown within the 3D alginate spheres presented spheroid morphology, optimal survival and proliferation capabilities, and a reduced sensitivity to the cytotoxic effect of imatinib mesylate. 3D cultured NB cells were also evaluated for the constitutive and IFN-γ-induced expression of surface molecules capable of tuning the anti-tumor activity of NK cells including immune checkpoint ligands. In particular, IFN-γ induced de novo expression of high amounts of HLA-I molecules, which protected NB cells from the attack mediated by KIR/KIR-L matched NK cells. Moreover, in the 3D alginate spheres, the cytokine increased the expression of the immune checkpoint ligands PD-Ls and B7-H3 while virtually abrogating that of PVR, a ligand of DNAM-1 activating receptor, whose expression correlates with high susceptibility to NK-mediated killing. Our 3D model highlighted molecular features that more closely resemble the immunophenotypic variants occurring in vivo and not fully appreciated in classical 2D culture conditions. Thus, based on our results, 3D hydrogel-based hydrogels might represent a clinical-relevant cell culture platform where to test the efficacy of personalized therapeutic approaches aimed to optimize the current and innovative immune based therapies in a very systematic and reliable way.